2017
DOI: 10.15244/pjoes/69444
|View full text |Cite
|
Sign up to set email alerts
|

Applying Landsat Satellite Thermal Images in the Analysis of Polish Lake Temperatures

Abstract: One of the basic parameters of water ecosystems is temperature. Its value and distribution are of key importance for the course of biotic and abiotic processes occurring in rivers and lakes. The issue of correlations of thermal conditions with the above elements is discussed by various scientific disciplines [1][2][3][4]. Proper interpretation of the occurring correlations requires possibly detailed data concerning water temperature. Such information is collected in various ways, and covers, among other things… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Current studies concerning lake water temperature in Poland [29][30][31] have not considered the effect of many factors (climatic, morphometric, hydrological) on its course and changes in a complex way. In order to fill this gap and investigate the most current conditions concerning the thermal regime of lakes in Poland, the objectives of this study were as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Current studies concerning lake water temperature in Poland [29][30][31] have not considered the effect of many factors (climatic, morphometric, hydrological) on its course and changes in a complex way. In order to fill this gap and investigate the most current conditions concerning the thermal regime of lakes in Poland, the objectives of this study were as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the urban heat island based on teledetection data have been conducted among others in Brno [13], Kraków [14], Madrid [15], and Poznań [16]. Moreover, satellite teledetection data are increasingly frequently used for the analysis of lake surface temperature [17,18] and dates of the beginning of the vegetative season [19].…”
Section: Introductionmentioning
confidence: 99%
“…Remote Sens. 2022, 14, 3839 3 of 22 obtained results revealed high cohesion with in situ measurements [35], encouraging a broader approach to the issue. Polish lakes already currently show a considerable increase in water temperature [29,36] that will continue to progress in the future [37,38].…”
Section: Methodsmentioning
confidence: 55%
“…No comprehensive research with the application of satellite images in reference to lake water temperature in Poland has been undertaken to date, although studies in the scope dynamically develop in different regions of the globe [31][32][33][34]. Polish research so far covers three lakes, and the obtained results revealed high cohesion with in situ measurements [35], encouraging a broader approach to the issue. Polish lakes already currently show a considerable increase in water temperature [29,36] that will continue to progress in the future [37,38].…”
Section: Introductionmentioning
confidence: 99%